Analysis Procedure For Credit in Efforts to Minimize Non Performing Loans on PT. Bank Lampung - Aminah AMINAH; Andi Darmawijaya (Universitas Bandar Lampung (UBL), 2015)
Credit procedures applied to lead to the achievement of the objectives of a business. Eachstage of the loan process must always be carried out by applying the precautionary principle. Lending procedures that will either be able to assist the bank in making the decision to grant. Credit employee is considered relatively safe because the installment payment system directly deducted from the salary did not rule out becoming jammed. This is due to mistakes made by employees in analyzing credit application file that led to the adoption of the standard operating procedures can not be run as designed. This study is a descriptive study using a qualitative approach. This qualitative descriptive study aimed to obtain information about the existing situation. In this study, will be described the following sources of information search behavior and tools. Discussion of this study are presented in narrative form words. The purpose of this study was to determine whether the procedures for granting credit at PT. Lampung Bank is in compliance with applicable regulations. From the results of research conducted, credit procedures at PT. Bank Lampung broadly in accordance with the Banking Act in terms of credit to the public. Lack of understanding of the types of loans that fit, lack of rigor in analyzing and evaluating credit applications, and lack of monitoring and intensive coaching against the debtor that cause non performing loans to the PT. Bank Lampung. Efforts to minimize the bad loans to the PT. Bank Lampung is good that the repeated restructuring, write-off of bad debts, termination billing, and procedures for the settlement of collateral items.